(untitled) (Revista de Física Médica, 2021)
Re-irradiation treatments are complex. Nowadays treatment planning systems have developed tools that allow image registration and add different dose plans on registered images. However, hypofractioned and accelerated treatments remain a challenge as evaluation of summed doses from different fractioning are difficult to understand. On this basis, treatment volume definition and dose prescription are sometimes limited and unclear. A tool has been developed to convert absorbed dose to Biologically Effective Dose and 2 Gy fractions equivalent dose. This tool creates a standard DICOM dose file that is possible to import on to the treatment planning system and allows the evaluation of summed dose plans with different fractioning. This works describes the tool creation and analyzes its clinical use. Results show a correct alignment between calculated dose matrices and the image set. It also shows limitations on the evaluation of point doses, especially in the boundaries of defined structures. Although this tool might be useful in a clinical environment an understanding of its limitations is required.